Sustainable Intensification of Tropical Agro-Ecosystems: Need and Potentials - Andres, Christian; Bhullar, Gurbir S. (Frontiers in Environmental Science, 2016)
Rapid population growth, increasingly complex economies and novel industrial uses of agricultural products call for further intensification of agriculture, particularly in the tropics. How to achieve sustainable intensification of food production systems in tropical regions that are challenged by ongoing climate change, loss of natural resources and biodiversity is a matter of debate. Here we highlight the major knowledge gaps in agricultural research and policy that must be addressed to develop adequate governance and regulatory frameworks for sustainable agricultural intensification. They include quantification of the i) value of (public/private) goods generated by ecosystem services, ii) costs to conserve the natural resources and biodiversity that maintain ecosystem services, and iii) true costs of different types of agriculture (in environmental, social and health dimensions) as well as iv) required adaptations that will make alternative farming strategies feasible at a global scale. We discuss the synergies and potential of agro-ecology and organic agriculture to transform our food systems and highlight the importance of controlling demand for food through societal (behavioral) and political (structural) changes in agricultural value chains. Finally, we review the sustainability standards and participatory guarantee systems in developed and developing countries, respectively, and argue that exemplars from developed countries could be role models in adapting governance and regulatory frameworks for developing countries.